(untitled) (Research, Society and Development, 2026)
Objective: To analyze the ecological relationship between the Human Development Index (HDI) and acute myocardial infarction (AMI) hospitalization rates in Brazil’s Center-West region (2020-2025). Methods: Ecological, retrospective, and quantitative study using data from the Unified Health System (SIH/SUS) and Atlas Brasil. Hospitalizations for AMI (ICD-10: I21) in elderly individuals (≥60 years) in Mato Grosso do Sul, Mato Grosso, Goiás, and Federal District were analyzed. Hospitalization rates per 100,000 inhabitants and Pearson correlation between the latest available Municipal HDI (2021) and municipal rates were calculated. Results: 50,667 hospitalizations were recorded. Goiás had the highest volume (25,715) and rate (356.8 per 100,000), followed by Mato Grosso do Sul (318.1). The Federal District, with the highest HDI (0.814), had an intermediate rate (255.7). Municipal analysis showed a significant positive correlation (r = 0.37; p = 0.011). Municipalities with higher HDI recorded higher hospitalization rates in the SUS. Conclusion: Municipalities with higher HDI showed higher hospitalization rates for AMI, suggesting direct influence of access to health services on hospital records. Findings contribute to understanding regional inequalities in access to cardiovascular care in the Unified Health System, providing support for planning public policies aimed at health equity.